2002
DOI: 10.1111/j.1574-6968.2002.tb11375.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thezwf-pgl-eda-operon inPseudomonas putidastrains H and KT2440

Abstract: A 3.9-kb fragment of the genome of Pseudomonas putida H, containing the complete zwf-pgl-eda-operon, encoding glucose 6-phosphate dehydrogenase, 6-phosphogluconolactonase and 2-keto-3-deoxy-6-phosphogluconate-aldolase, respectively, and part of the divergently transcribed regulatory gene, hexR, was cloned and analyzed. The nucleotide sequences of these genes showed high similarities to the corresponding DNA sequences of P. putida KT2440 and also to sequences of Pseudomonas aeruginosa PAO1. Derivatives of strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Complementing previous studies on the global hexose metabolism repressor, HexR, in P. putida [21-24], our results suggested that involvement of HexR in regulation of lsc expression might be a selective adaptation of the plant pathogen, P. syringae , to its well-studied infection cycle [42,43]. Once Lsc is secreted, cellular resources needed for its synthesis such as amino acyl residues are not available for the cell anymore.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Complementing previous studies on the global hexose metabolism repressor, HexR, in P. putida [21-24], our results suggested that involvement of HexR in regulation of lsc expression might be a selective adaptation of the plant pathogen, P. syringae , to its well-studied infection cycle [42,43]. Once Lsc is secreted, cellular resources needed for its synthesis such as amino acyl residues are not available for the cell anymore.…”
Section: Discussionsupporting
confidence: 80%
“…Analysis of the nucleotide sequences upstream of lscB and lscC , which are almost identical at nucleotide level [2,40], revealed the presence of a sequence (nucleotides +113 to +127 with respect to the corresponding translational start site) with high similarity to the conserved motif TTGTN 7–8 ACAA previously shown to be the DNA binding site of HexR in P. putida [22-24] (Figure 1). This finding suggested a putative binding of HexR of P. syringae to the upstream sequence of both lsc genes.
Figure 1 Nucleotide sequence of the upstream region of lscB .
…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the genomes of G. sulfurreducens and most other Geobacteraceae , which encode the enzymes of only the non-oxidative branch of the pentose phosphate pathway, the G. metallireducens genome includes a cluster of oxidative pentose phosphate pathway enzyme genes: 6-phosphogluconolactonase (Gmet_2618, 30% identical to the Pseudomonas putida enzyme [82]), glucose-6-phosphate dehydrogenase (Gmet_2619, 50% identical to the Nostoc punctiforme enzyme [83]), and 6-phosphogluconate dehydrogenase (Gmet_2620, 36% identical to YqeC of B. subtilis [84]), along with two ribose-5-phosphate isomerase isoenzymes (Gmet_2621 and Gmet_1604 = GSU1606, 39% and 44% identical to RpiB of E. coli [85]). Thus, G. metallireducens apparently generates biosynthetic reducing equivalents in the form of NADPH from carbohydrates.…”
Section: Resultsmentioning
confidence: 99%
“…In Pseudomonas species, glycolysis is linked with the EntnerDoudoroff (ED) pathway, which is extensively studied in Pseudomonas putida and contains two operons (zwf-pgl-eda and eddglk-gltR2-gltS) (55). The transcription of these operons is controlled by the repressor HexR, which directly binds to an inverted repeat (TTGTN 7-8 ACAA) in these two promoters, which is released by the specific binding of the ED pathway intermediate 2-keto-3-deoxy-6-phosphogluconate (KDPG) to HexR (24).…”
Section: One-dose-based Microarray Analyses (Highlighted In Red Inmentioning
confidence: 99%